Crassiflorone derivatives that inhibit Trypanosoma brucei glyceraldehyde-3-phosphate dehydrogenase (TbGAPDH) and Trypanosoma cruzi trypanothione reductase (TcTR) and display trypanocidal activity - Uliassi, Elisa; Krauth-Siegel, Renate (European journal of medicinal chemistry, 2017)
Crassiflorone is a natural product with anti-mycobacterial and anti-gonorrhoeal properties, isolated from the stem bark of the African ebony tree Diospyros crassiflora. We noticed that its pentacyclic core possesses structural resemblance to the quinone-coumarin hybrid 3, which we reported to exhibit a dual-targeted inhibitory profile towards Trypanosoma brucei glyceraldehyde-3-phosphate dehydrogenase (TbGAPDH) and Trypanosoma cruzi trypanothione reductase (TcTR). Following this basic idea, we synthesized a small library of crassiflorone derivatives 15-23 and investigated their potential as anti-trypanosomatid agents. 19 is the only compound of the series showing a balanced dual profile at 10 μM (% inhibitionTbGAPDH = 64% and % inhibitionTcTR = 65%). In phenotypic assay, the most active compounds were 18 and 21, which at 5 μM inhibited Tb bloodstream-form growth by 29% and 38%, respectively. Notably, all the newly synthesized compounds at 10 μM did not affect viability and the status of mitochondria in human A549 and 786-O cell lines, respectively. However, further optimization that addresses metabolic liabilities including solubility, as well as cytochromes P450 (CYP1A2, CYP2C9, CYP2C19, and CYP2D6) inhibition, is required before this class of natural product-derived compounds can be further progressed.